Publishing journal articles - Becker, Lucinda M. (Success in research., 2012)
This book offers down-to-Earth advice on such vital topics as: How to write and get the style right What to select for publication How to plan for success How to cope with writer's block Working with editors and reviewers How to cope with rejection This is a must-have book for anyone seeking to write for successful journal publication. Practical, no-nonsense, accessible guide to planning, writing and publishing a journal article.